Organizational Learning Culture, Consumer Satisfaction and Employee’s Attitude: Causality Analysis - Junita, Audia (Department of Management, Faculty of Economics, Universitas Negeri Semarang, 2017)
This research was conducted to explore the organizational learning culture in banking and its effect on customer satisfaction with the employee’s attitude as the intervening variable. The re-search was performed in Bank Syariah Mandiri’s business unit of Medan Region. The research design used hypothesis testing. The samples of this research were 52 frontline employees and 140 customers of Bank Syariah Mandiri in Medan Region. Primary data was collected by using a questionnaire. The data were analyzed using path analysis. Results support that Bank Syariah Mandiri as State-owned enterprises in the field of financial services has implemented good or-ganizational learning culture. Organizational learning culture has significant effect to customer satisfaction through employee’s job satisfaction and organizational commitment. The attitudes of employees are integrated important intervening variables in mediating the relationship be-tween organizational learning culture and customer satisfaction. The role of attitude in medi-ating the influence of organizational learning culture to worker’s service behavior, in order to create consumer satisfaction in the banking sector, proven empirically.